Abacavir causes leukocyte/platelet crosstalk by activating neutrophil P2X7 receptors thus releasing soluble lectin‐like oxidized low‐density lipoprotein receptor‐1. (18th January 2023) - Blanch‐Ruíz, Maria Amparo; Sánchez‐López, Ainhoa; Ríos‐Navarro, César; Ortega‐Luna, Raquel; Collado‐Díaz, Víctor; Orden, Samuel; Martínez‐Cuesta, María Angeles; Esplugues, Juan V.; Álvarez, Ángeles
Abstract : Background and Purpose: Abacavir, an antiretroviral drug used in HIV therapy associated with myocardial infarction, promotes thrombosis through P2X7 receptors. The role of platelets as pro‐thrombotic cells is acknowledged whereas that of neutrophils—due to their secretory capacity—is gaining recognition. This study analyses the role of neutrophils—specifically the secretome of abacavir‐treated neutrophils (SNABC )—in platelet activation that precedes thrombosis. Experimental Approach: Effects of abacavir or SNABC on platelet activation and platelet–leukocyte interactions and expression of lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1) were analysed by flow cytometry. The secretome was analysed by proteomics. The role of leukocytes in the actions of abacavir was evaluated in a mouse model of thrombosis. Key Results: Abacavir induced platelet–leukocyte interactions, not directly via effects of abacavir on platelets, but via activation of neutrophils, which triggered interactions between platelet P‐selectin and neutrophil P‐selectin glycoprotein ligand‐1 (PSGL‐1). SNABC stimulated platelet activation and platelet–leukocyte interactions through a process that was dependent on LOX‐1, neutrophil P2X7 and platelet P2Y1, P2Y12 and P2X1 receptors. Abacavir induced the expression of LOX‐1 on neutrophils and of the soluble form of LOX‐1 (sLOX‐1) in SNABC . Neutrophils, LOX‐1, P2X7, P2Y1, P2Y12 and P2X1 receptors were required for the pro‐thrombotic actions of abacavir in vivo. Conclusion and Implications: Neutrophils are target cells in abacavir‐induced thrombosis. Abacavir released sLOX‐1 from neutrophils via activation of their P2X7 receptors, which in turn activated platelets. Hence, sLOX‐1 could be the missing link in the cardiovascular risk associated with abacavir. Abstract :